Energy consumption as a condition for per capita carbon dioxide emission growth: The results of a qualitative comparative analysis in the European Union. (August 2019) - Loures, L.; Ferreira, P.
Abstract: The problematic of climatic changes and the respective consequences raises the need to discuss the problem and define measures to control and/or reverse them. Because one of the causes of climatic changes is the emission of greenhouse gases, the European Union defined the reduction of emissions as a main concern as well as increasing efficiency in the energy sector. With the objective of analysing the main conditions affecting the growth of per capita emissions, this paper uses a fuzzy-set qualitative comparative analysis (fsQCA). Based on a sample of data from 2010 to 2014, the conditions evaluated were: i) GDP growth; ii) change in the share of GDP relating to private consumption; iii) change in the share of GDP relating to public consumption; iv) change in the share of GDP on investment; v) and energy consumption growth. The main drivers contributing to reduced emissions were the crisis and energy consumption. Evaluation of the main factors affecting emissions growth is the main contribution of this study. Considering that economic growth is an obvious goal, the European Union must design measures encouraging investment in more efficient and less pollutant technologies, which is also in accordance with OECD sustainability goals. Highlights: Fuzzy-set qualitative comparative analysis is used to study emission growth in the European Union. The main drivers of reduced emissions were the economic crisis and energy consumption. The results are important for policy makers in order to redesign their strategies. It is crucial to start investing in more efficient and less pollutant technologies.